Damage to enteric neurons occurs in mice that develop fatty liver disease but not diabetes in response to a high‐fat diet. Issue 8 (23rd June 2014) - Rivera, L. R.; Leung, C.; Pustovit, R. V.; Hunne, B. L.; Andrikopoulos, S.; Herath, C.; Testro, A.; Angus, P. W.; Furness, J. B.
Abstract Background Disorders of gastrointestinal functions that are controlled by enteric neurons commonly accompany fatty liver disease. Established fatty liver disease is associated with diabetes, which itself induces enteric neuron damage. Here, we investigate the relationship between fatty liver disease and enteric neuropathy, in animals fed a high‐fat, high‐cholesterol diet in the absence of diabetes. Methods Mice were fed a high‐fat, high‐cholesterol diet (21% fat, 2% cholesterol) or normal chow for 33 weeks. Liver injury was assessed by hematoxylin and eosin, picrosirius red staining, and measurement of plasma alanine aminotransaminase (ALT). Quantitative immunohistochemistry was performed for different types of enteric neurons. Key Results The mice developed steatosis, steatohepatitis, fibrosis, and a 10‐fold increase in plasma ALT, indicative of liver disease. Oral glucose tolerance was unchanged. Loss and damage to enteric neurons occurred in the myenteric plexus of ileum, cecum, and colon. Total numbers of neurons were reduced by 15–30% and neurons expressing nitric oxide synthase were reduced by 20–40%. The RNA regulating protein, Hu, became more concentrated in the nuclei of enteric neurons after high‐fat feeding, which is an indication of stress on the enteric nervous system. There was also disruption of the neuronal cytoskeletal protein, neurofilament medium. Conclusions & Inferences Enteric neuron loss and damage occurs in animals with fatty liver disease in the absence of glucose intolerance. The enteric neuron damage may contribute to the gastrointestinal complications of fatty liver disease.